Dynamics of particulate organic carbon mobilization, storage, and export across river sedimentary systems - Hilton, RG; Schwab, M; Galy, V (Elsevier, 2024)
River particulate organic carbon (POC) plays a central role in the global carbon cycle, while its geochemical composition has provided insight on the functioning of the terrestrial biosphere and soils. Here we review the isotopic composition of river POC (stable isotopes and radiocarbon) and organic biomarkers found in river sediments and discuss how these reflect varied sources of organic matter delivered to river systems by hydrological and geomorphic processes. Subsequent hydrodynamic sorting in river channels, alongside biogeochemical processing and sediment deposition also impact the fluxes and composition of river POC. A first order separation of POC into biospheric and rock-derived components allows us to quantify global export by rivers to the oceans (biospheric POC = 0.18+0.07/−0.05 PgC year−1, petrogenic POC = 0.04+0.06/−0.03 PgC year−1) and evaluate impacts on carbon cycling. However, we emphasize that biospheric POC is itself a diverse mixture of organic matter sourced from plants, soils and aquatic productivity. A recent shift in paradigm has shown that biospheric POC can be highly reactive and turnover on annual to decadal timescales, contributing actively to the contemporary carbon cycle. Here we discuss the tectonic, climatic and anthropogenic drivers of POC erosion, supply and river export. River POC plays a key role in the sedimentary cycle of carbon over 103–106 timescales, while we suggest riverine transfer of biospheric POC could amount to an important component of the anthropogenic C budget.